The differential diagnosis in nonlymphoproliferative malignant pleural effusion cytopathology and its correlation with patients' demographics - Erika F. Rodriguez (2018)
© 2018 S. Karger AG, Basel. Background: We report our experience with malignant pleural effusion (MPE) and the impact of patients' demographics on the differential diagnosis at the primary site. Methods: After IRB approval, we searched our pathology database from January 2013 to January 2017 for patients with positive pleural effusions (PEs). Patients' demographics and clinical histories were noted. Results: 474 patients were identified (288 females [61%] and 186 males [39%]), ranging in age from 19 to 64 years old. Ethnicity was distributed as follows: Caucasian (n = 330, 70%), African American (n = 114, 24%) and Asian (n = 30, 6%). The most common primary sites were the lung (n = 180, 37%), followed by the breast (n = 81, 17%), and the gynecologic system (67, 13%). The lung was the most common primary for all ethnicities (n = 190, 40%). The second-most common primary site was the breast in African Americans and Caucasians and upper gastrointestinal (GI) tract in Asians. In 5 cases (1%), the primary tumor could not be determined. Conclusion: Cytology examination is a useful method to diagnose primary sites of PE. Pulmonary primary is the most common cause of effusion in all ethnicities. In African American and Caucasian patients, the breast was the second-most common site of MPE, while in Asian patients it was the upper GI tract.